Stage IA Patients With Pancreatic Ductal Adenocarcinoma Cannot Benefit From Chemotherapy: A Propensity Score Matching Study - Zhang, Yuchao; Xu, Gang; Chen, Maozhen; Wei, Qian; Zhou, Tengteng; Chen, Ziliang; Shen, Mingyang; Wang, Ping (Frontiers in Oncology, 2020)
Purpose: Adjuvant chemotherapy is recommended for all patients with pancreatic ductal adenocarcinoma (PDAC) following resection by the clinical practice guidelines. This study aimed to evaluate the efficacy of adjuvant chemotherapy among the staging groups of the American Joint Committee on Cancer (AJCC) for PDAC. Patients and methods: This retrospective cohort analysis was performed by the Surveillance Epidemiology and End Results (2004-2015) database and multi-institutional dataset (2010-2018). Baseline clinicopathologic characteristics of PDAC patients, including age, gender, ethnicity, marital status, education level, county income level, county unemployed rate, insurance status, grade, stage, chemotherapy and radiotherapy, were collected. Overall survival (OS) was analyzed using the Kaplan-Meier method. The SEER and multi-institutional data were adjusted with 1:1 ratio propensity score matching (PSM). Results: In total, 6274 and 1361 PDAC patients were included from the SEER database and multi-institutional dataset, respectively. Regardless of the count of resected lymph nodes, adjuvant chemotherapy prolonged the long-term OS time for stage IB, IIA, IIB and III patients in both SEER and multi-institutional cohorts. Nevertheless, adjuvant chemotherapy did not provide additional clinical benefits even after a PSM adjustment for stage IA patients in both SEER and multi-institutional cohorts. Conclusion: Adjuvant chemotherapy improved the long-term survival of stage IB, IIA, IIB and III PDAC patients; however, it demonstrated no survival benefit on stage IA PDAC patients. Thus, adjuvant chemotherapy should not be recommended for stage IA PDAC patients. These would significantly reduce the economic burden of society and improve the life quality of stage IA PDAC patients.